Endoscopic negative pressure therapy for leaks with large cavities in the upper gastrointestinal tract: is it a feasible therapeutic option? - Kouladouros, Konstantinos; Belle, Sebastian; Reißfelder, Christoph; Kähler, Georg (Scandinavian journal of gastroenterology, 2021)
Background Endoscopic negative pressure therapy (ENPT) is an increasingly popular method for the treatment of various defects of the upper and lower gastrointestinal (GI) tract and has been associated with high success rates. The largest reported series focus on intraluminal therapy of local defects, whereas larger defects connected to the abdominal or pleural cavity are still regarded as indications for surgical revision in many units. The aim of our study is to assess the efficacy and the periinterventional characteristics of ENPT applications in patients with defects with large cavities in the upper GI tract. Methods We retrospectively analysed all cases of ENPT applications in the upper gastrointestinal tract performed in our clinic between 1 January 2010 and 31 December 2019 and identified the patients with defects leading to large cavities with a length of at least 7 cm. The procedural characteristics, intraprocedural and late complications and overall clinical success were analysed. Results We identified 14 cases meeting our inclusion criteria. In all cases, an intracavitary or combined intracavitary and intraluminal ENPT was applied. The average duration of therapy was 47.5 days and included an average of 10.4 changes per patient in an interval of 4.5 days. Clinical success rate was 92.9%, average hospital stay was 74.5 days. In three cases, a late stenosis occurred, which could be treated endoscopically. Conclusion Based on the data of our case series, we conclude that ENPT is a feasible and promising therapeutic option for upper GI defects with contact to large cavities.
Gesehen am 31.03.2021
Published online: 17 Dec 2020